PENGELOLAAN DAN PENGEMBANGAN KEGIATAN EKTRAKURIKULER DI SMA NEGERI 1 KUANTAN HILIR SEBERANG - Masyhur, Masyhur; Yasmawati, Yasmawati; Fahreni, Rhena (Jurnal Manajemen Pendidikan, 2020)
The aim of this research is to 1) know the management of extracurricular activities at SMA Negeri 1 Kuantan Hilir Seberang; 2) know the innovation extracurricular activities in the development of character in students of SMA Negeri 1 Kuantan Hilir Seberang; 3) know the shape of the character development of students in extracurricular activities at SMA Negeri 1 Kuantan Hilir Seberang. This type of research in this study is a descriptive qualitative approach using observations, interviews, and documentation. The result of this research shows that extracurricular management and extracurricular development at SMA Negeri 1 Kuantan Hilir Seberang can achieve goals through planning, organizing, controlling, and monitoring. Self-development and innovation activities carried out through these extracurricular can impact the development of the character of students, such as confidence, discipline, responsibility, hard work, self-reliance, empathy, better academic abilities, better educational satisfaction, and higher self-concept.